2009
DOI: 10.1074/jbc.m805962200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants for Interfacial Binding and Conformational Change in a Soluble Diacylglycerol Kinase

Abstract: DgkB is a soluble diacylglycerol (DAG) kinase that is essential for membrane lipid homeostasis in many Gram-positive pathogens. Anionic phospholipids, like phosphatidylglycerol (PtdGro), were required for DgkB to recognize diacylglycerol embedded in a phospholipid bilayer. An activity-independent vesicle binding assay was used to determine the role of specific residues in DgkB-PtdGro interactions. Lys 15 and Lys 165 were required for DgkB to dock with PtdGro vesicles and flank the entrance to the DgkB active s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The DgkB surface is overall electronegative, except for an electropositive patch consisting of Lys15, Arg20, and Lys165 adjacent to the active site entrance. DgkB binds to anionic phospholipid vesicles with high affinity, and analysis of the K15A, R20A, and K165A mutant proteins confirm the role of these residues in interfacial docking [99]. Binding of DgkB to anionic phospholipids lowers the K m for ATP from 3.7 mM to 32 μM illustrating that interfacial binding triggers a conformational change that activates the kinase.…”
Section: Phospholipid Recyclingmentioning
confidence: 99%
“…The DgkB surface is overall electronegative, except for an electropositive patch consisting of Lys15, Arg20, and Lys165 adjacent to the active site entrance. DgkB binds to anionic phospholipid vesicles with high affinity, and analysis of the K15A, R20A, and K165A mutant proteins confirm the role of these residues in interfacial docking [99]. Binding of DgkB to anionic phospholipids lowers the K m for ATP from 3.7 mM to 32 μM illustrating that interfacial binding triggers a conformational change that activates the kinase.…”
Section: Phospholipid Recyclingmentioning
confidence: 99%
“…This soluble DAG kinase is highly specific for the phosphorylation of DAG over other phospholipids, and its primary sequence places it in the same protein family as the mammalian signaling DAG kinases. Unlike the integral membrane DgkA, DgkB is an interfacial enzyme that uses positively charged lysine residues on its surface to dock on the anionic surface of the cell membrane [138]. This property is demonstrated in vitro through enzymatic assays showing a robust increase in DgkB activity when DAG is incorporated into negatively-charged PtdGro vesicles, as opposed to neutrally charged bilayers [138].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the integral membrane DgkA, DgkB is an interfacial enzyme that uses positively charged lysine residues on its surface to dock on the anionic surface of the cell membrane [138]. This property is demonstrated in vitro through enzymatic assays showing a robust increase in DgkB activity when DAG is incorporated into negatively-charged PtdGro vesicles, as opposed to neutrally charged bilayers [138]. Complementation studies of a dgkB mutant with an inducible plasmid expressing dgkB revealed the gene to be essential in B. subtilis unless LTA synthesis is disrupted by mutations in yflE, a gene homologous to ltaS of S. aureus.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced sensitivity (~10×) that we observed is consistent with what was reported using the AlphaScreen platform compared with other assay formats for other targets as well. 31,32 The donor and acceptor beads contain multiple binding sites, and thus the enhanced sensitivity of this platform is attributed to a bead avidity effect. The bead avidity effect allows for weak interactions (in the 50-100 µM range) to be successfully measured using this format.…”
Section: Discussionmentioning
confidence: 99%